Copper antimony sulfide thin films for visible to near infrared photodetector applications. Issue 54 (4th September 2018) - Vinayakumar, V.; Shaji, S.; Avellaneda, D.; Aguilar-Martínez, J. A.; Krishnan, B.
Abstract : Copper antimony sulfide (CuSbS2 ) thin films for visible to near infrared photodetection Abstract : Ternary chalcostibite copper antimony sulfide (CuSbS2 ) is an emerging semiconductor material having applications in photovoltaics, energy storage and optoelectronics due to its high absorption coefficient, suitable bandgap, and it consists of non-toxic and earth abundant elements. CuSbS2 thin films are prepared by combining chemical bath deposition (antimony sulfide (Sb2 S3 )) and thermal evaporation (copper (Cu)) followed by a heat treatment and their application as visible to near infrared photodetectors is reported. Crystalline structure, elemental composition, chemical state, morphology and optoelectronic properties of the films were characterized by various techniques. The effect of three different Cu thicknesses (CAS 20, CAS 30 and CAS 40 nm) on the photodetection properties are evaluated under illumination using light emitting diodes (LEDs) and a laser. The photodetectors fabricated are successfully tested under different wavelengths, power densities and applied voltage and their photoresponse cyclic stability for each wavelength of illumination was recorded. From the sensitivity calculations, the sample with 20 nm Cu thickness (CAS 20) showed higher detection sensitivity for visible to near infrared wavelengths. Better responsivity results were obtained for CAS 40 because of its improved crystallinity and phase purity. Photodetector properties such as sensitivity and responsivity are evaluated for all the samples. These results are beneficial for cost effective and environment friendly photodetectors and optoelectronic devices based on CuSbS2 thin films.